Biomechanics in Dentistry: Evaluation of Different Surgical Approaches to Treat Atrophic Maxilla Patients - Ishak, Muhammad Ikman; Abdul Kadir, Mohammed Rafiq (SpringerBriefs in Computational Mechanics, 2013)
This book shows computational finite element simulations to analyse the strength of implant anchorage for intrasinus and extramaxillary approaches under various occlusal loading locations and directions. Three-dimensional model of the craniofacial area surrounding the region of interest, soft tissue and framework are developed using computed tomography image datasets.  The zygomatic and standard dental implants are modeled using a conventional computer-aided design software and placed at the appropriate location.  Material properties are assigned appropriately for the cortical, cancellous bones and implants with Masseter forces applied at the zygomatic arch and occlusal loadings applied on the framework surface.